A Toll‐Like Receptor 1/2 Agonist Augments Contractility in Rat Corpus Cavernosum. (31st July 2015) - Stallmann‐Jorgensen, Inger; Ogbi, Safia; Szasz, Theodora; Webb, R. Clinton
Abstract Introduction Activation of the innate immune Toll‐like receptor 2 (TLR2) initiates inflammation and has been implicated in vascular dysfunction. Increased contraction and decreased relaxation responses in the penile vasculature lead to erectile dysfunction, a condition associated with inflammation. However, whether TLR2 activation plays a role in penile vascular function has not been established. Aim We hypothesized that activation of the TLR 1/2 heterodimer (TLR1/2) augments contractile and impairs relaxation responses of corpus cavernosum and that these perturbations of vascular function are mediated by low nitric oxide (NO) availability and enhanced activity of the RhoA/Rho‐kinase pathway. Methods Contraction and relaxation responses were measured in rat cavernosal strips using a myograph after incubation with a TLR1/2‐activating ligand Pam3CSK4 (Pam3), the TLR1/2 inhibitor CuCPT 22 (CuCPT), and inhibitors of NO synthase (LNAME) and Rho‐kinase (Y27632). TLR2 protein expression was assessed by immunohistochemistry. Main Outcome Measures Cumulative concentration response curves, sensitivity (pEC50), and maximal response (Emax) of cavernosal strips to vasodilatory and vasocontractile agonists were compared between treatments. Results Pam3‐treated cavernosal strips exhibited greater pEC50 and higher Emax to phenylephrine (PE) than control tissues. Inhibition of NO synthase increased Emax to PE in Pam3‐treated cavernosal strips. Pam3 treatment reduced relaxation to Y27632 compared with control tissues. Inhibition of TLR1/2 activation with CuCPT returned the augmented contraction to PE and the decreased relaxation to Y27632 of Pam3‐treated cavernosal strips to control values. Conclusions The TLR1/2 heterodimer mediates augmented contraction and reduced relaxation in rat cavernosal strips. Thus, TLR1/2 activation antagonizes vascular responses crucial for normal erectile function and implicates immune activation in vasculogenic erectile dysfunction. Immune signaling via TLR2 may offer novel targets for treating inflammation‐mediated vascular dysfunction in the penis. Stallmann‐Jorgensen I, Ogbi S, Szasz T, and Webb RC. A Toll‐like receptor 1/2 agonist augments contractility in rat corpus cavernosum. J Sex Med 2015;12:1722–1731.